STRENGTHENING NATIONALISM VALUES IN SOCIAL SCIENCES LEARNING AT STATE MIDDLE SCHOOL 10, SORONG DISTRICT - Pintje Falila; Sudrajat Sudrajat; Raras Gistha Rosardi Gistha Rosardi (Indonesian Journal of Social Science Education (IJSSE), 2026)
ABSTRACT: Nationalism remains one of the most pressing character-education goals in Indonesian schools, particularly in regions where dual identity presents a structural challenge to civic cohesion. This qualitative descriptive study examines how Social Studies (IPS) teachers at SMP Negeri 10, Sorong Regency, Papua, strengthen nationalism values through classroom instruction, and what obstacles they face in doing so. Data were gathered through semi structured interviews with the school principal, an extracurricular supervisor, three IPS teachers, and twelve students, supplemented by non-participant classroom observation and document analysis of lesson plans and curriculum materials. Thematic analysis reveals three interconnected findings. First, the teacher applies the structured three-phase approach of planning, execution, and evaluation. Second, learners reflect measurable understanding, though uneven, of the indicators, but is reflected in the concrete behavior of the class. Third, the four categories that are the roadblock to teacher competence gap, extra curriculum burdens, the limitations of infrastructure tools, and the lack of emphasis from families which collectively reduces the depth of nationalism study. The study argues that cultural response, structured professional development of teachers, and a closer partnership between school and family are essential requirements for sustainable nationalism education in a diverse ethnic border community.